Моделювання реакції ґрунтів на сейсмічні впливи для забезпечення сейсмостійкості споруд за європейськими стандартами (за матеріалами наукового повідомлення на засіданні Президії НАН України 30 травня 2018 р.) - Семенова, Ю.В. (Вісник НАН України, 2018)
Розвинуто методику визначення резонансних властивостей ґрунтів під
будівельними майданчиками з урахуванням нелінійних ефектів, в основі
якої лежить аналітично-емпіричний підхід до розрахунку частотних характеристик ґрунтів. Удосконалено методику побудови частотних характеристик ґрунтових комплексів для сейсмічного мікрорайонування майданчиків у сейсмічних районах України з метою її узгодження з
рекомендаціями європейських будівельних стандартів «Єврокод-8». Удосконалену методику визначення резонансних властивостей ґрунтів впроваджено при визначенні сейсмічної небезпеки майданчиків ряду наявних і
проектованих об'єктів, таких як ГЕС, АЕС, висотні житлові та експериментальні будинки, громадські центри, газоперекачувальні станції тощо. In the article the task of accounting for resonant and non-linear effects in soils during seismic microzoning of construction
and operation sites is solved. The method of determining the resonant properties of soils while accounting for their
nonlinearity for the purpose of seismic proof designing of buildings and structures on the construction sites of Ukraine is
developed and introduced into practical application. The developed method is based on an analytical-empirical approach
for calculating the frequency characteristics of soils. Improved method of constructing of the frequency characteristics of
ground is necessary for adjusting the methods of seismic microzoning of areas of buildings and industrial structures placement
in seismic regions of Ukraine with the regulatory requirements of European standards “Eurocode-8”. The method
of calculating the frequency characteristics of soils is based on forming computational models of soil strata using their
empirical deformation characteristics and application of mathematical equivalent linear and nonlinear modeling of soil
response to seismic influences. The construction of seismic calculation models uses strain-dependent shear modulus and
damping ratio from the database which comprises the deformation properties of different soil types typical for sites located
in Ukraine. The improved method for determining the resonance properties of soils has been implemented in the
determination of seismic hazard of sites of a number of existing and projected objects, such as hydroelectric power plants,
nuclear power plants, high-rise housing and experimental buildings, public centers, gas transmission stations, etc.